ANALYSIS OF FINANCIAL RATIOS TO FINANCIAL PERFORMANCE AT PT BANK CIMB NIAGA TBK - Mendrofa, Tuberta Rosviani; Sihotang, Dian Putri; Sitompul, Elisabeth Magdalena; Hasugian, Christnova; Siallagan, Hamonangan (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
Analysis of financial ratios on the financial performance of PT Bank CIMB Niaga Tbk for the 2021-2022 period, with a focus on the importance of financial management in achieving maximum profits. The method used is quantitative descriptive with secondary data taken from financial reports accessed through the Indonesian Stock Exchange. The analysis results show that the bank's liquidity ratio is very good, with a Current Ratio (CR) above 200% in 2021 (465.51%) and 2022 (509.05%), which indicates the ability to meet short-term obligations. However, the solvency ratio shows a poor condition, with the Debt to Equity Ratio (DER) above 100% (616.29% in 2021 and 577.52% in 2022), indicating a high debt burden compared to own capital. In addition, the profitability ratio, as measured by Return on Assets (ROA), is below the standard 5% (1.3% in 2021 and 1.7% in 2022), indicating an inability to generate profits from the assets owned. This research suggests that banks optimize assets, reduce debt, and increase the efficiency of management costs to improve financial performance.